Clothing Degree Zero: A Late Reading of Barthes’ Fashion ‘System - Jie, Feng (Theory, culture & society, 2020)
Drawing upon Roland Barthes’ posthumously published notebooks from his 1974 trip to China, in which he remarks upon the ‘complete absence of fashion. Clothing degree zero’, this article offers a ‘late’ reading of Barthes’ interest in fashion, suggested here as a form of writing. In reference to the late works, specifically Barthes’ penultimate lecture course on the Neutral and Travels in China, supplemented by François Jullien’s comments on Barthes’ trip to China (regarding the use of the term ‘blandness’), as well as mention of Michelangelo Antonioni’s film Chung Kuo-Cina (which Barthes viewed with ‘methodological’ interest), it is possible to draw together a reading of fashion as a neutral form. As a final step, reflection is given to Susan Buck-Morss’ reading of ‘history as passing’, as discontinuous moments (whereby fashion is symptomatic of such transformations). Barthes’ writerly mode – which works upon incidental details (also found in the work of Antonioni) – is revealed to be a pertinent method.